The high blood: lineage consciousness and the texts of Pedro Afonso of Barcelos (14th century): O alto sangue: a consciência de linhagem e os escritos de Pedro Afonso de Barcelos (século XIV) (Revista de História da UEG (REVHIST), 2024)
“A man of high blood from both parts of where he came from”. With these words Pedro Afonso (1287-1354), Count of Barcelos and bastard of King Dom Dinis I (1261-1325), wrote the panegyric of Dom Mudarra – but what did this quality attributed by that Portuguese history mean? Here we explore in the count’s texts what the historian Georges Duby defined as a “consciousness of lineage”, that is, a way in which the medieval noble strata identified themselves based on their kinship ties. Our hypothesis is that the expression attributed to that noble knight “of very high blood” carried at its core a principle of historicity – in Dom Mudarra the past of his ancestors was recognized as an active agent, an honor founded in the kinship structures of that society.Keywords: Medieval historiography. Nobility. Iberian Peninsula.